Recurrences and progression following microsurgery of vestibular schwannoma - Scheer, Maximilian; Simmermacher, Sebastian; Prell, Julian; Leisz, Sandra; Scheller, Christian; Mawrin, Christian; Strauss, Christian; Rampp, Stefan (Frontiers in Surgery, 2023)
Background: The treatment approach of vestibular schwannoma (VS) has seen a change in recent years, with a trend away from radical surgery towards preservation of cranial nerve function. A recent study reported recurrences as long as 20 years after complete removal of VS. Objective: To report the risk of recurrence and progression in our patient population the authors retrospectively reviewed outcomes of patients. Methods: Cases with unilateral VS who had undergone primary microsurgery via retrosigmoidal approach between 1995 and 2021 were investigated. Complete tumor removal was defined as gross total resection (GTR), a capsular remnant was categorized as near total resection (NTR) and residual tumor was designated as subtotal resection (STR). The primary endpoint was radiological recurrence-free survival. Results: 386 patients fulfilled the inclusion criteria of the study and were evaluated. GTR was achieved in 284 patients (73.6%), NTR was achieved in 63 patients (10.1%) and STR was present in 39 patients (16.3%). A total of 28 patients experienced recurrences with significant differences in the three subgroups. The strongest predictor of recurrence was the extent of resection, with patients who underwent STR having an almost 10-fold higher risk of recurrence and patients who had undergone NTR having an almost 3-fold higher risk than those treated with GTR. More than 20% of recurrences (6/28) occured after more than 5 years. Conclusion: The degree of resection is an important guide to the interval of follow-up, but long-term follow-up should be considered also in the case of GTR. The majority of recurrences occurs after 3-5 years. Nevertheless, a follow-up of at least 10 years should be carried out.